High bisphenol A concentrations augment the invasiveness of tumor cells through Snail-1/Cx43/ERRγ-dependent epithelial-mesenchymal transition. (February 2020) - Ryszawy, Damian; Pudełek, Maciej; Kochanowski, Paweł; Janik-Olchawa, Natalia; Bogusz, Joanna; Rąpała, Michał; Koczurkiewicz, Paulina; Mikołajczyk, Justyna; Borek, Izabela; Kędracka-Krok, Sylwia; Karnas, Elżbieta; Zuba-Surma, Ewa; et al.
Abstract: Bisphenol A (BPA) is commonly present in plastics used for food storage and preservation. The release of BPA from these products results in a permanent human exposition to BPA; however, the quality and quantity of BPA adverse effects remain a matter of controversy. The common presence of BPA in the human environment and the controversies concerning the relations of human exposition to BPA and cancer incidence justify the research on the interactions between BPA and pro-metastatic signaling in cancer cells. Here, we describe a novel BPA-reactive signaling axis that induces the epithelial-mesenchymal transition (EMT) in lung adenocarcinoma A549 cells. BPA exerted negligible effects on their properties in a wide range of concentrations (10 nM - 100 nM), whereas it considerably induced A549 invasiveness at high concentrations (10 μM). The BPA-induced EMT was illustrated by morphologic changes, E/N-cadherin switch and vimentin/Snail-1/connexin(Cx)43 up-regulation in A549 populations. It was followed by enhancement of A549 drug-resistance. Corresponding effects of BPA were observed in prostate cancer cell populations. Concomitantly, we observed increased levels and perinuclear accumulation of estrogen-related receptor gamma (ERRγ) in BPA-treated cells, its interactions with Cx43/Snail-1, and the corresponding effects of phenol red on A549 cells. Collectively, these data identify a novel, pro-metastatic Snail-1/Cx43/ERRγ signaling pathway. Its reactivity to BPA underlies the induction of cancer cells' invasiveness in the presence of high BPA concentrations in vitro. Thus, the chronic exposition of cancer cells to extrinsic and intrinsic BPA should be considered as a potential obstacle in a cancer therapy. Highlights: BPA increases invasiveness of lung cancer cells. EMT accounts for BPA-induced augmentation of lung cancer cells' invasiveness. Cooperative Snail-1/Cx43/ERRγ signaling is involved in the BPA-induced EMT of A549 cells. Snail-1/Cx43/ERRγ axis induces reprogramming and chemoresistance of cancer cells. BPA induces pro-invasive effects when applied at very high concentrations.